Amazing Agent Luna omnibus II. Vol. 4-5 - DeFilippis, Nunzio (Seven Seas, 2009)
"Agent Luna has been undercover at Nobel High School for most the school year ... With her secret [identity] on the verge of being exposed Luna begins a dangerous alliance with Jonah --who may also turn out to be her first boyfriend ..."--Cover.